The Role of Nutrition in HIV-Associated Neurocognitive Disorders: Mechanisms, Risks, and Interventions - Carlotta Siddi; Jihane Balla; Christy Agbey; Paola Fadda; Simona Dedoni (Life, 2025)
HIV-associated neurocognitive disorders (HANDs) refer to a range of cognitive deficits that afflict people living with the Human Immunodeficiency Virus (HIV). The fundamental processes of HAND include persistent inflammation, immunological activation, and direct viral impact on the central nervous system. Emerging research shows that nutritional status, especially food consumption and body weight, is critical in determining the course and severity of HAND. Malnutrition exacerbates neurocognitive impairment by increasing inflammation and oxidative stress, while obesity may contribute to HAND through the promotion of metabolic disruption, gut microbiota alterations, and systemic inflammation. Additionally, the introduction of antiretroviral treatment (ART) has substantially enhanced the prognosis of people living with HIV by lowering viral load and improving immune function. However, depending on the regimen, ART can cause changes in body weight, which may influence the progression of HAND. This emphasizes the intricate interplay between HIV, nutrition, body weight, and neurocognitive health. As a result, various dietary approaches are currently being investigated to improve the quality of life of individuals with HIV and possibly help prevent neurocognitive decline in this population. This review aims to elucidate the relationship between nutrition and neurocognitive function in individuals living with HIV, shedding light on aspects of HANDs related to diet, body weight fluctuations, and metabolic syndrome. It explores the shift from current pharmacological treatments to innovative non-pharmacological interventions, including specific dietary strategies, to support overall health and cognitive well being in HIV-positive people.